THE EXPANSION OF THE RANGE OF MOUSSES OF DIABETIC APPOINTMENTS - Tatyana Vasilevna Kalashnova; Irina Aleksandrovna Belyaeva (Современная наука и инновации)
The innovative composition of mousses has been developed, that includes full replacement of such component as water, on freshly squeezed fruit juices of strawberry, cranberry, lingonberry and sour milk drinks with added fructose. Thanks to it mousses get a new taste, enriched with vitamins, minerals and meet the requirements of the diet in diabetes by all odds.